1966
DOI: 10.1063/1.1754655
|View full text |Cite
|
Sign up to set email alerts
|

Self-Induced Divergence of Cw Laser Beams in Liquids— A New Nonlinear Effect in the Propagation of Light

Abstract: Articles you may be interested inEffects of backward-propagating waves and lumped mirror losses on self-induced transparency modelocking in quantum cascade lasers Appl. Phys. Lett. 95, 071109 (2009); 10.1063/1.3206741Self-induced nonlinear Zernike filter realized with optically addressed liquid crystal spatial light modulator

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
96
0
2

Year Published

1977
1977
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(102 citation statements)
references
References 9 publications
4
96
0
2
Order By: Relevance
“…5 In 1966 Reickhoff reported irradiance-dependent self-defocusing in liquids. 6 One year later Leite et al demonstrated an optical limiter that used thermal blooming in nitrobenzene and, along with a spatial filter, regulated the output power of a cw Ar laser to 30 mW. 7 In 1980 CS 2 was tested as a limiting medium.…”
Section: Introductionmentioning
confidence: 99%
“…5 In 1966 Reickhoff reported irradiance-dependent self-defocusing in liquids. 6 One year later Leite et al demonstrated an optical limiter that used thermal blooming in nitrobenzene and, along with a spatial filter, regulated the output power of a cw Ar laser to 30 mW. 7 In 1980 CS 2 was tested as a limiting medium.…”
Section: Introductionmentioning
confidence: 99%
“…Так, характерной чертой тепло вой само(де)фокусировки осесимметричного лазер ного пучка в жидкостях является вертикальный ас тигматизм прошедшего пучка, растущий с интенсив ностью излучения и связанный с конвекцией при сильном лазерном нагреве [76][77][78]. Тепловые нели нейные линзы в элементах резонаторов непрерыв ных и импульсных лазеров могут оказывать сущест венное влияние на модовую структуру [7,75] и ди намику генерации лазера [65], а также проявляются в тонкой структуре спектра излучения [83,95]. Теп ловые линзы наряду с нелинейными линзами в жид ких кристаллах при ориентации директора [35] яв ляются одним из наиболее простых и ярких демонст раций эффекта нелинейной линзы [64].…”
Section: "тонкиеunclassified
“…2. Приближенный расчет фокусного расстояния нелинейной линзы F HJI через поперечный размер ' и стрелку прогиба вол нового фронта ных непрерывных газовых лазеров [64][65][66].…”
unclassified
“…The earliest experiments employing the thermal lens effect were conducted within the laser resonating cavity [22,24,25]; however, the difficulty in conducting these kinds of intracavity experiments quickly led to the development of extracavity experiments [26]. Initially, intracavity and extracavity experiments employed a single laser for thermal lens generation and signal quantification.…”
Section: Introductionmentioning
confidence: 99%